In memory of Lourdes Taboada, teacher of teachers. (Journal of Parents and Teachers, 2014)
This article is a tribute to Lourdes Taboada, teacher of Early Childhood Education and Rural Schools in Galicia. She, a reference in innovation, a recognized advisor in education and author of a rich written production, receives in these sheets a tribute to her memory and a remind that her work must continue, even though she is no longer among us.
Keywords: Tribute; Lourdes Taboada; educational innovation; referent; teacher; children's education; rural schools.